Questions for Amma: Tracing the manifestations of violence on the South African Indian Female body - Naicker, Kivithra (Department of Drama, 2019)
“[i]n the eyes of the law, a woman is both Eve and Eva. As a pure, fragile female she must be specially protected; as a seductive object, from whom men must be protected. In both cases women are the victims” (Navi Pillay in Gqola, 2015: 36). This research investigates performance as a medium through which the South African Indian female body transgresses and transcends the limitations and barriers of identity, culture and society. As this study positions the brown female body as a site for violence and codification, it challenges the mythical and stereotypically gendered representations of brown females in media and culture. In examining the performance of gender through the performative case studies supporting this research, this study critically engages with the fluid and shifting territory of identity and culture, tracing a feminist tradition beyond western notions, challenging overlooked cultural and domestic injustices which perpetuate a culture of patriarchy. Rape culture thrives on manufacturing power and fear, with rape being “sexualised violence” that has “survived as long as it has because it works to keep patriarchy intact” (Gqola, 2015: 21). Through performance, this study documents the manifestations of violence on the brown female body, theoretically engaging with how subtle and surreptitious forms of violence work to reinforce patriarchy playing into rape culture, perpetuating a cycle of oppression. In examining the 'tradition’ of Indian theatre in South Africa, this research examines the theatrical devices used to express anxieties, crisis of identity and representation, focusing on the South African Indian female experience through an auto-ethnographical study interrogating my identity and position as a South African Indian (Hindu-Tamil) female, artist, and feminist scholar. This study also unpacks the complexities and contradictions embedded within the representations of the brown female body in theatre, 'Indian’ and Hindu culture through a feminist lens, arguing that gender stereotypes perpetuate a cycle of oppression; highlighting ways in which the brown female body is trained and disciplined into performing as an Indian woman.